Biotin-functionalized copolymeric PEG-PCL micelles for in vivo tumour-targeted delivery of artemisinin. Issue 1 (4th December 2019) - Nosrati, Hamed; Barzegari, Parisa; Danafar, Hossein; Kheiri Manjili, Hamidreza
Abstract: Artemisinin is used as an antimalarial and anticancer agent with minimal toxic effects on the host body. Biotin-PEG-PCL polymers have been used for targeted drug delivery to cancer, as well as to improve the pharmacokinetics of the drug and reduce its effects. In this study, biotin-conjugated copolymers were fabricated with polymerization of the ring opening method and the properties of copolymer and nanoparticles were investigated using various techniques. The toxicity of artemisinin and its nanoparticles have been investigated on MCF-7 and normal HFF2 cells. The results showed that the encapsulation efficacy of artemisinin in nanoparticles was 45.5 ± 0.41%. The release profile of the drug indicates that the release is slow and controlled and is approximately pH dependent. The results of artemisinin cell culture on human breast cancer cells showed that biotin-PEG-PCL nanoparticles had an inhibitory effect on MCF-7 cells and had no toxic effects on HFF2 cells. Anticancer activity in vivo in the 4T1 breast cancer model showed that tumour volumes were decreased up 40 mm 3 by ART-loaded micelles and 76 mm 3 by free ART, compared to the control group (2150 mm). In vivo results showed that this formulation significantly increases the accumulation of substances in the tumours. Therefore, the molecular formulation of ART-based copolymers can be a desirable process for cancer treatment purposes.